ANALYSIS OF LEADERSHIP INFLUENCE AND ACHIEVEMENT MOTIVATION ON PERFORMANCE OF EMPLOYMENT POLITECHNIC EMPLOYEES IN DEPOK - Isidorus Anung Prabadhi (Jurnal Ilmiah Kajian Keimigrasian, 2018)
Organization requires human resources capable of running its activities properly so as to achieve the objectives set.Leadership and achievement motivation becomes one of the factors that can affect the performance of employees in carrying out its activities. This study aims to identify and analyze the influence of leadership and achievement motivation on employee performance either partially or simultaneously. This research uses a design causal or causal population numbers are all employees of the Polytechnic of Immigration Depok. Probability sampling technique is saturated with a sample of 33 employees. The analytical method used is multiple linear regression analysis. The results showed that simultaneous (test F) leadership and achievement motivation has a positive and significant influence on employee performance. Partial test results showed that the variable of leadership has a positive and significant influence on employee performance at the Polytechnic of Immigration, Depok. Achievement motivation has a positive and significant influence on employee performance Immigration Polytechnic.